Novel Fe3O4@metal-organic framework@polymer core-shell-shell nanospheres for fast extraction and specific preconcentration of nine organophosphorus pesticides from complex matrices. (15th December 2021) - Wan, Mengfei; Xiang, Fachun; Liu, Zhongdong; Guan, Denggao; Shao, Yong; Zheng, Lufei; Jin, Maojun; She, Yongxin; Cao, Liping; Jin, Fen; Chen, Rui; Wang, Shanshan; et al.
Graphical abstract: Highlights: A novel Fe3 O4 @ZIF-8@polymer core-shell-shell nanosphere was fabricated via a facile and versatile modification strategy. Functional polymer modification substantially improved the extraction performance of Fe3 O4 @ZIF-8 for OPPs. Magnetic core endowed fast separation and simplified the pre-treatment process. A high sensitive and reliable MSPE-LC/MS-MS method was developed and validated. It can be used for simultaneous monitoring of multiple OPPs in various matrices at trace levels. Abstract: Herein, a novel core-shell-shell magnetic nanosphere denoted as Fe3 O4 @ZIF-8@polymer was fabricated by sequential in situ self-assembly and precipitation polymerization for effective magnetic solid-phase extraction of nine organophosphorus pesticides (OPPs) from river water, pear, and cabbage samples. The integrated Fe3 O4 @ZIF-8@polymer featured convenient magnetic separation property and excellent multi-target binding ability. More importantly, the functional polymer coating greatly improved the extraction performance of Fe3 O4 @ZIF-8 for OPPs, thus facilitating the simultaneous determination of trace OPP residues in real samples. The developed MPSE-LC-MS/MS method exhibited good linearity ( R 2 ≥ 0.9991) over the concentration range of 0.2–200 µg L −1, low limits of detection of 0.0002–0.005 μg L −1 for river water and 0.006–0.185 μg kg −1 for pear and cabbage, satisfactory precision with relative standard deviations ≤ 9.7% and accuracy with recoveries of 69.5–94.3%. These results highlight that the combination of polymers with MOFs has great potential to fabricate excellent adsorbents for high-throughput analysis of various contaminants in complex matrices.